A new approach to superstring field theory - Berkovits, Nathan Jacob [UNESP] (Wiley-Blackwell, 2000)
I review the construction of an action for open superstring field theory which does not suffer from the contact term problems of other approaches. I also discuss a possible generalization of this action for closed superstring field theory.